2016
DOI: 10.1038/mtm.2016.69
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of proliferating cells from CNS grafts using a Ki67 promoter-driven thymidine kinase

Abstract: Pluripotent stem cell (PSC)-based cell therapy is an attractive concept for neurodegenerative diseases, but can lead to tumor formation. This is particularly relevant as proliferating neural precursors rather than postmitotic mature neurons need to be transplanted. Thus, safety mechanisms to eliminate proliferating cells are needed. Here, we propose a suicide gene approach, based on cell cycle-dependent promoter Ki67-driven expression of herpes simplex virus thymidine kinase (HSV-TK). We generated a PSC line e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…We observed a significant increase in the amount of cells during maturation from an NPC to a mature neuronal state (Fig, 6c). Although further analysis at longer time-points is certainly required, we consider this result as an in-vitro confirmation of the potential risk of in-vivo tumorigenesis, one of the main challenges associated with transplantation NPCs 86,87 . Our results highlight the need for tight control of proliferation and terminal differentiation.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…We observed a significant increase in the amount of cells during maturation from an NPC to a mature neuronal state (Fig, 6c). Although further analysis at longer time-points is certainly required, we consider this result as an in-vitro confirmation of the potential risk of in-vivo tumorigenesis, one of the main challenges associated with transplantation NPCs 86,87 . Our results highlight the need for tight control of proliferation and terminal differentiation.…”
Section: Discussionmentioning
confidence: 60%
“…Our results highlight the need for tight control of proliferation and terminal differentiation. This underscores the importance of emerging approaches such as the incorporation of a suicide gene for proliferating cells into the graft 86 , selection of a suitable progenitor population, expressing specific surface ventral midbrain markers 88 , or by trans-differentiation of more mature cells 89 . It also underpins the importance of approaches such as the one investigated here that enable prolonged maturation prior to implantation, offering the possibility of later quality control points.…”
Section: Discussionmentioning
confidence: 99%
“…S4). Previous studies have demonstrated that the HSV‐TK/GCV suicide system ablated teratomas in an efficient and specific manner ; however, one recent study reported GCV resistance partially due to escape mutations in HSV‐TK . The experimental parameters differed between these studies, including the iPSC or embryonic stem cell (ESC) lines, cell preparation, promoter, gene integration method, HSV‐TK variant, onset and duration of GCV treatment after cell transplantation, GCV dose, route of GCV administration, and observation period.…”
Section: Discussionmentioning
confidence: 99%
“…This therapy can selectively kill actively proliferating cancer cells, including undifferentiated tumorigenic cells. Lentivirus-transduced and undifferentiated hPSCs expressing the HSV-tk gene are effectively eliminated in vitro in the presence of GCV 19, 20. In addition, in vivo teratomas derived from HSV-tk- transduced hPSCs shrink following the administration of GCV.…”
Section: Main Textmentioning
confidence: 99%